Appointment as Paper Reviewer for National Research & Innovation Conference for Graduate Students in Social Sciences 2014 - Fatahyah, Yahya (Universiti Putra Malaysia, 2014)
The document contains an appointment letter as a Paper Reviewer for National Research & Innovation Conference for Graduate Students in Social Sciences 2014